2012
DOI: 10.1111/j.1708-8305.2012.00619.x
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Ciguatera Fish Poisoning on a Cargo Ship in the Port of Hamburg

Abstract: Sailors are an occupational group at risk for ciguatera fish poisoning due to potentially unsafe food sources during international travel. Even if no fatality occurred, the disease affected marine operations due to high attack rates and chronicity of symptoms. Medical doctors must be aware that ciguatera fish poisoning is a risk for seafarers traveling in tropical and subtropical areas. Stocking of food in affected ports from safe sources, adequate training of ship cooks, and informing sailors about the risk o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 4 publications
0
15
0
1
Order By: Relevance
“…If food specimens are available they can be collected and tested for presence of ciguatera toxin. There is no antidote for ciguatera poisoning, and people who have consumed ciguatoxin receive symptomatic treatment (6). Most people suffering from ciguatera fish poisoning will recover completely within a few days or weeks, but in very rare cases, ciguatera can be fatal (4).…”
Section: Discussionmentioning
confidence: 99%
“…If food specimens are available they can be collected and tested for presence of ciguatera toxin. There is no antidote for ciguatera poisoning, and people who have consumed ciguatoxin receive symptomatic treatment (6). Most people suffering from ciguatera fish poisoning will recover completely within a few days or weeks, but in very rare cases, ciguatera can be fatal (4).…”
Section: Discussionmentioning
confidence: 99%
“…CTXs resist extreme temperature, weak acid treatments and alkaline conditions [2,9] and not destroyed by any preserved methods [10]. Mechanistically, the primary mode of action of the toxin is via binding to site 5 of the mammalian voltage-gated sodium channels in excitable tissues.…”
Section: Ciguatera Poisoningmentioning
confidence: 99%
“…It has been suggested that even <0.1 ppb of CTX in fish tissue constitutes a risk of poisoning with attack rates around 80-90% [5,7]. In the course of CFP, gastrointestinal symptoms initially occur followed by neurological events.…”
mentioning
confidence: 99%
“…Ideally, CFP is confirmed by laboratory testing of fish remains for the presence of CTX. Poisoning is not a result of improper handling of fish, but rather due to CTX bioaccumulation through the food chain [7].…”
mentioning
confidence: 99%
See 1 more Smart Citation